Lactation Duration and Long-term Risk for Incident Type 2 Diabetes in Women With a History of Gestational Diabetes Mellitus - Ley, Sylvia H. (Diabetes Care, 2020)
OBJECTIVE: We examined the association of lactation duration with incident type 2 diabetes among women with a history of gestational diabetes mellitus (GDM). RESEARCH DESIGN AND METHODS: We monitored 4,372 women with a history of GDM participating in the Nurses’ Health Study II for incident type 2 diabetes over 25 years up to 2017. Lactation history was obtained through follow-up questionnaires to calculate lactation duration. Follow-up blood samples were collected from a subset of these women at median age of 58 years through the Diabetes & Women’s Health Study. RESULTS: We documented 873 incident cases of type 2 diabetes during 87,411 person-years of follow-up. Longer duration of lactation was associated with lower risk of type 2 diabetes for both total lactation (hazard ratio 1.05 [95% CI 0.83–1.34] for up to 6 months, 0.91 [0.72–1.16] for 6–12 months, 0.85 [0.67–1.06] for 12–24 months, and 0.73 [0.57–0.93] for >24 months, compared with 0 months; P-trend = 0.003) and exclusive breastfeeding (P-trend = 0.002) after adjustment for age, ethnicity, family history of diabetes, parity, age at first birth, smoking, diet quality, physical activity, and prepregnancy BMI. Longer duration of lactation was also associated with lower HbA(1c), fasting plasma insulin, and C-peptide concentrations among women without type 2 diabetes at follow-up (all adjusted P-trend ≤0.04). CONCLUSIONS: Longer duration of lactation is associated with a lower risk of type 2 diabetes and a favorable glucose metabolic biomarker profile among women with a history of GDM. The underlying mechanisms and impact on diabetes complications, morbidity, and mortality remain to be determined.